A COMPARATIVE POLITICAL ANALYSIS BETWEEN THE NEW ORDER REGIME AND THE REFORMED ERA IN INDONESIA: A CASE STUDY OF OLIGARCHY POLITICS IN THE MINING INDUSTRY OF EAST KALIMANTAN - PRATAMA, PRAWIRA YUDHA; BUDIMAN, BUDIMAN; SARMIASIH, MIA (Universitas Muhammadiyah Yogyakarta, 2019)
This study analyzes and discusses the democratization of the political oligarchy circle in assessing comparative political oligarchy between the new order (ORBA) and the reformed regime. The authors used a literature review method, which is through journals and reports that associate the goal of this research and had descriptively designed the study through data obtained from the said sources. Findings generated in this study are the comparison between the state of political oligarchy in the new era and the post-reform era. Seen over time, the democratization process increasingly shows a paradoxical situation. It illustrates that the political dynamics and democratic freedoms of citizens are being controlled, as a reflection of perplexed democracy perceived with detachment during the New Order authoritarian regime. Political actors also have taken advantage of the transition building a consolidated political force and repositioning itself into a storefront network of governmental power. However, the transition process aided the rise of a black-market democracy – entrepreneur oligarchs whose hunger for political power and wealth brought them to control the growth and direction of democracy. A problem that this research wants to examine.